(untitled) (Vietnam Journal of Community Medicine, 2022)
Objective: This study was intended to assess the Anopheles mosquito species composition, density which was a malaria transmission in Ia Hdreh commune, Krong Pa district, Gia Lai province. Subject and method of the study: Anopheles mosquito population in Ia Hdreh commune, Krong Pa district, Gia Lai province was collected from October 2019 to June 2020 by insect investigation method. Result: 11 Anopheles species were collected. An.drirus and An.minimus were the primary malaria vectors.